Pendampingan Pengembangan Video Animasi Berbasis Instagram Reels Pada Materi HIV Untuk Meningkatkan Literasi Kesehatan Siswa Kelas X MAN Manggarai Barat Labuan Bajo - Fidyah Febrianti; As’ad Syamsul Arifin (Inisiatif : Jurnal Dedikasi Pengabdian Masyarakat, 2026)
This community service research aims to develop an animated video learning media based on Instagram Reels on the Human Immunodeficiency Virus (HIV) material for grade X students of MAN Manggarai Barat Labuan Bajo and to determine the level of media feasibility based on expert validation and student responses. This community service research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments are in the form of a material expert validation questionnaire, a media expert validation questionnaire, and a student response questionnaire using a Likert scale. The data analysis technique is carried out descriptively quantitatively by calculating the percentage of media feasibility. The results show that the animated video media based on Instagram Reels obtained a very feasible category based on material expert validation with a percentage of 89% and media expert validation with a percentage of 91%. In addition, student responses obtained a percentage of 88% with a very good category. The developed media is considered interesting, easy to understand, interactive, and able to increase student learning motivation on HIV material. The use of Instagram Reels as a learning medium also provides a flexible learning experience and is in accordance with the characteristics of the digital generation. Thus, Instagram Reels-based animated video media is suitable for use as an alternative digital based biology learning media for abstract material.